(untitled) (Social and Environmental Law Journal, 2025)
This research aims to analyze agrarian crimes and their repercussions on the Brazilian and Goiás contexts of violence and criminality in rural areas, by identifying the structure of repression of rural crimes in Brazil and Goiás. The main objective is to discuss the difficulties in combating crime in the rural environment, considering crimes against property in rural areas. The research discusses the development of public security policies to combat property crimes in rural areas. Additionally, it evaluates data related to theft and robbery crimes recorded at the Rural Crimes Police Station of Goiás between 2017 and 2021. Through documentary research using a qualitative methodology, the study observes positive results obtained by the public policy of integration between the public security agencies of the State of Goiás and other bodies involved with agribusiness, as well as the participation of the private sector and the population.